Pesquisa científica na educação básica: educação e preservação ambiental da biodiversidade costeira do município de Bertioga - Mota, Verena Camargo (2020)
This research presents techniques for experimental practice in teaching the disciplines that make up the area of Natural Sciences and its Technologies, in high school. Proposing the analysis of the natural environments surrounding the school units, as study alternatives, applying specific knowledge in the context of the student's life, valuing his previous knowledge and bringing him closer to scientific knowledge, through the work of socio-environmental research and concern for quality of life of community residents, by identifying the presence of lead, in the waters of the Itapanhaú River, in the municipality of Bertioga, on the coast of São Paulo. The authors supporting this work: Myriam Krasilschik (2011), Nelio Bizzo (2009), Berenice Alvares Rosito (2011), Ione Maria de Oliveira et.al. (2006), as well as official publications BNCC (2018) and CONAMA. Support the results from the perspective constructivist, proving that apply science in a practical way is possible in public school, what subjects (problem situations) of common interest such as the "health of the River", encourage the active participation of students and thus, result in the awareness of the interactions between science and society as a complex activity and that there is no universal method for solving all problems, but an interactive dynamic between thought and action. Keywords: Bertioga; Itapanhaú River; Teaching Practice; BNCC; Lead.